PENGARUH TATA KELOLA PERUSAHAAN, KESEMPATAN BERTUMBUH, KEPEMILIKAN INSTITUSIONAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Dimas, Dimas Salman Al Farisi; Hasnawati; M.Malik (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study aims to examine the effect of corporate governance, growth opportunities, institutional ownership, and profitability on firm value. The sample used in this study is an energy company listed on the Indonesia Stock Exchange in 2021-2023 with 186 observations obtained using purposive sampling techniques. This study uses a panel data regression analysis method using Eviews 12. The results of this study prove that profitability has a positive effect on firm value. Meanwhile, corporate governance, growth opportunities, and Institutional Ownership do not affect firm value. The results of this study simultaneously prove that corporate governance, growth opportunities, Institutional Ownership, and profitability affect firm value. The implications of this study suggest that companies should prioritize increasing profits through operational efficiency and sustainable business strategies, as this approach has been proven to increase company value and attract investors. Furthermore, even if corporate management and other factors do not significantly impact profitability, companies must ensure effective management practices, consider shareholder interests, and adapt to external changes such as technological advances, economic conditions, and government regulations to maintain long-term stability.